WAYS TO DEVELOP CREATIVE ABILITIES OF GIFTED STUDENTS - Toshpo'latov Xumoyun Rahmatillo o'g'li (Journals Park Publishing, 2024)
The article discusses modern methods of developing the creativity of gifted students, improving the efficiency of technical creativity using a variety of methods, and ways to develop the creative abilities of gifted students.
Keywords: student, talented student, podcast, TED Talks, creative skills, conversation, technical, technical creativity, teacher, teaching process.